Intestinal ischaemia associated with phaeochromocytoma. - Carr, N. D. (BMJ Group, 1989)
The present case report describes a patient with an adrenal phaeochromocytoma who presented with infarction of the small intestine. The clinical features, diagnosis and treatment of this case are described. Despite excision of the tumour and necrotic intestine, this patient died in the postoperative period from overwhelming sepsis and multi-organ failure. Special reference is made to the delayed effects of established intestinal ischaemia on immune function and it is suggested that this was major contributory factor to the fatal outcome in the present case. The onset of gastro-intestinal symptoms in patients with phaeochromocytoma should suggest the possibility of imminent gut ischaemia and indicate the necessity for prompt excision of the tumour.